Examining and predicting land use change dynamics in Gandhinagar district, Gujarat, India - Ekta Purswani; Satyam Verma; S. Jayakumar; M. L. Khan; Bhawana Pathak (Journal of Urban Management, 2022)
Urbanization is gaining pace worldwide and is the most elemental cause of global land transformation. This necessitates land use land cover change to be analyzed on various spatial and temporal scales to understand its potential impacts on the environment. This work focuses on the urbanization in the area of Gandhinagar district, Gujarat, India which encloses Gandhinagar, the capital city of Gujarat. Though a capital, the city has seen limited growth and development since its formation in 1961. Land use change was analyzed from 1995 to 2016 and land change modeling was attempted to generate future prediction scenarios in 2025 using the IDRISI TERRSET Land change modeler. The change analysis revealed vast growth in rural and urban built-up, majorly, at the expense of agriculture, slightly contributed by the decline in scrubland. There is much scope for urban densification as urban built-up occupies only about 5% of the total land cover as observed by the land use land cover map of 2016. The growth of the city has been very slow as compared to the other cities of its time due to a state-centric approach. But the projected scenario discovered a faster sprawl-like built-up growth towards the urban areas in the west and the south instead of an isodiametric aggregation around the capital city due to an arbitrary planning system. We recommend bringing all the talukas in Gandhinagar under one roof and considering the development of the whole district in scope for better policy and management.
Keywords: 710; Land change modeling; Land use change; Markov chain analysis; Remote sensing; Urbanization